GANGGGUAN DEPRESIF ORGANIK PADA WANITA DENGAN KEGANASAN GINEKOLOGI STADIUM LANJUT: SEBUAH SERIAL KASUS - Silaen, Rebecca Mutia Agustina; Darmayasa, I Made; Ariani, Ni Ketut Putri (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Cervical and ovarian cancers often give rise to significant psychological impacts, including depressive disorders. In certain conditions, depression emerges as a direct consequence of biological changes resulting from the underlying physical illness. This case series report describes two female patients diagnosed with advanced-stage gynecological malignancies who met the criteria for organic depressive disorder, aiming to illustrate the clinical manifestations, diagnostic process, and management of organic depressive disorder in women with advanced gynecological malignancies. The study utilized data obtained through medical record review, clinical and ancillary examinations, as well as interviews with the patients and their families, which were subsequently analyzed descriptively and narratively. The research stages included case identification, assessment of depression severity using the Hamilton Depression Rating Scale, establishment of the diagnosis, and implementation of pharmacological and non-pharmacological palliative interventions. Both cases fulfilled the criteria for organic depressive disorder and were managed using a comprehensive palliative approach. It is concluded that organic depressive disorder represents an important complication of advanced gynecological malignancies and requires holistic management to improve patients’ quality of life. ABSTRAK Kanker serviks dan ovarium sering menimbulkan dampak psikologis yang bermakna, termasuk gangguan depresif. Pada kondisi tertentu, depresi muncul sebagai akibat langsung dari perubahan biologis akibat penyakit fisik yang mendasari. Laporan kasus serial ini menjelaskan dua pasien wanita yang didiagnosis keganasan ginekologi stadium lanjut dan memenuhi kriteria gangguan depresif organik, yang bertujuan untuk menggambarkan manifestasi klinis, proses diagnosis, dan penatalaksanaan gangguan depresif organik pada wanita dengan keganasan ginekologi stadium lanjut, menggunakan data yang diperoleh melalui telaah rekam medis, pemeriksaan klinis dan penunjang, serta wawancara dengan pasien dan keluarga, kemudian dianalisis secara deskriptif dan naratif. Tahapan penelitian meliputi identifikasi kasus, penilaian derajat depresi menggunakan Hamilton Depression Rating Scale, penetapan diagnosis, serta pemberian intervensi paliatif farmakologis dan nonfarmakologis. Kedua kasus memenuhi kriteria gangguan depresif organik dan ditangani dengan pendekatan paliatif komprehensif. Disimpulkan bahwa gangguan depresif organik merupakan komplikasi penting pada keganasan ginekologi stadium lanjut yang memerlukan penatalaksanaan holistik untuk meningkatkan kualitas hidup pasien.